2018
DOI: 10.20471/acc.2018.57.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Ultrasound Measurement of Muscle Thickness In Patients with Supraspinatus Tendon Pathology

Abstract: SUMMARY – Objectives of the study were to observe supraspinatus muscle thickness in patients with supraspinatus tendon pathology using ultrasound (US) and examining inter- and intra-rater reliability, and to compare muscle thickness with cross-sectional area (CSA) and occupation ratio measured by both US and magnetic resonance imaging (MRI). The investigation was designed as a prospective cohort study. Two groups of patients were included in the study: 43 patients with tendon rupture and 44 patients without te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…According to the literature, several methods have been described and studied to identify PM thickness. However, studies assessing the cut-off and validity standard of PM thickness to track PS condition have not been conducted (10)(11)(12)(13)(14). In this study, we found that the AUROC of PM thickness was 0.970 (95% CI 0.943-0.998, p < 0.05), suggesting that the PM thickness was a good predictor of PS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…According to the literature, several methods have been described and studied to identify PM thickness. However, studies assessing the cut-off and validity standard of PM thickness to track PS condition have not been conducted (10)(11)(12)(13)(14). In this study, we found that the AUROC of PM thickness was 0.970 (95% CI 0.943-0.998, p < 0.05), suggesting that the PM thickness was a good predictor of PS.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, few studies have shown that US measurement of muscle thickness is reliable for musculoskeletal pathology diagnosis, such as in patients with supraspinatus tendon pathology by Kretić et al ( 12 ) and thigh muscle thickness for the assessment of sarcopenia by Hida et al ( 13 ). Hence, we suggest that the US-guided measurement of PM thickness is one of the major diagnostic criteria for PS.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 In these previous studies, the atrophy of SSP muscle was assessed by the occupation ratio with US; cross-sectional area of SSP muscle belly divided by the surface area of scapular fossa. 17 , 18 , 19 , 20 However, the agreement between occupation ratio measured by US and MRI was 0.43 shown by Kim et al., 20 and 0.90byKhoury et al. 17 Thus, discrepancy was reported for this agreement.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the measurement of muscle thickness could be a more suitable evaluation for muscle atrophy in clinical practice.Asinprevious literatures, the correlation between muscle thickness of SSP measured by US and the cross-sectional area using MRI was 0.60, and 0.76. 19 , 21 Nevertheless, little research has been conducted to showthe agreement betweenthe cross-sectional area of ISP and TM measured by MRIandthe muscle thicknessmeasuredby US. Also, the muscle thickness of SSP was evaluated at the scapular notch.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 According to our data, arthrosis of the clavicular-acromial joint is one of the most common causes of pain in the shoulder joint during rehabilitation in patients after a suture of a partial rupture of the tendon of the supraspinatus muscle of the shoulder. [14][15][16][17] Pain in the clavicular-acromial joint in patients after a suture of the rotator cuff of the shoulder disrupts to development of movements in the shoulder joint, increases the duration of rehabilitation, and worsens the overall results of treatment. In the English-language literature, we did not find works devoted to damage to the tendon of the supraspinatus muscle against the background of deforming arthrosis of the clavicular-acromial joint.…”
Section: Introductionmentioning
confidence: 99%